In silico analysis of selected alkaloids against main protease (Mpro) of SARS-CoV-2. (1st December 2020) - Garg, Saksham; Roy, Arpita
Abstract: In the present situation, COVID-19 has become the global health concern due to its high contagious nature. It initially appeared in December 2019 in Wuhan, China and now affected more than 190 countries. As of now preventive measures are the sole solution to stop this disease for further transmission from person to person transmissions as there is no effective treatment or vaccine available to date. Research and development of new molecule is a laborious process; therefore, drug repurposing can be an alternative solution that involves the identification of potential compounds from the already available data. Alkaloids are potential source of therapeutic agents which might be able to treat novel COVID-19. Therefore, in the present study, twenty potential alkaloid molecules that possess antiviral activity against different viral diseases have taken into consideration and scrutinized using Lipinski's rule. Then out of twenty compounds seventeen were further selected for docking study. Docking study was performed using Autodock software and the best four molecule which provides maximum negative binding energy was selected for further analysis. Two alkaloids namely thalimonine and sophaline D showed potential activity to inhibit the M pro but to confirm the claim further in-vitro studies are required.